Pengembangan media pocket book JAHITAN berbasis kearifan lokal pada materi matematika kelas IX SMP - Istiqomah, Maulida; Bulkani, Bulkani; Putra, Chandra Anugrah (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2025)
Low mathematics learning outcomes at the junior high school level indicate that the learning media used are not yet contextualized to students’ local experiences. This research aimed to develop the JAHITAN Pocket Book, grounded in local wisdom, as a mathematics learning resource that meets the criteria of validity, practicality, and effectiveness. This study applied an R&D method using the ADDIE framework, consisting of five sequential phases, i.e., analysis, design, development, implementation, and evaluation. The participants consisted of 17 ninth-grade students from SMP Negeri Satu Atap 2 Kuala Pembuang. The validation phase indicated that the product was highly feasible, receiving 100% from material experts, 80% from media experts, and 90% from language experts. The practicality assessment received an average of 96% from teachers and 87.18% from students, both of which were classified as very practical. Meanwhile, the effectiveness evaluation on cognitive outcomes reached 78%, supported by an N-Gain value of 0.78 in the high category. Non-cognitive aspects also showed effectiveness, with learning enthusiasm at 90%, activeness at 90.20%, and skills at 94.31%. These results indicated that the locally grounded Pocket Book JAHITAN is feasible to use as a mathematics learning medium that enhances students’ learning outcomes and character development.